Allergen‐specific immunotherapy induces regulatory T cells in an atopic dermatitis mouse model. Issue 9 (16th May 2018) - Shin, J. U.; Kim, S. H.; Noh, J. Y.; Kim, J. H.; Kim, H. R.; Jeong, K. Y.; Park, K. H.; Lee, J.; Chu, H.; Lee, J.‐H.; Yong, T.‐S.; Park, J.‐W.; et al.
Abstract: Background: Several studies have demonstrated that allergen‐specific immunotherapy (SIT) can be an effective treatment for atopic dermatitis (AD). However, there is no relevant mouse model to investigate the mechanism and validate the novel modality of SIT in AD. Methods: NC/Nga mice with induced AD‐like skin lesions received a subcutaneous injection of SIT (an extract of the house dust mite Dermatophagoides farinae [ DfE ]) or placebo for 5 weeks). Clinical and histological improvements of AD‐like skin lesions were examined. The responses of local and systemic regulatory T (Treg) cells, natural killer (NK) cells, B cells, serum immunoglobulin, and T‐cell cytokine response to DfE were evaluated to determine the underlying mechanism of the observed results. Results: Specific immunotherapy significantly improved AD‐like skin lesions. Histologically, SIT decreased epidermal thickness and reduced inflammatory cell infiltration, especially that of eosinophils. Concomitantly, SIT suppressed Th2 responses and induced local infiltration of Treg cells into the skin. Also, SIT induced the immunoglobulin G4 and attenuated allergen‐specific immunoglobulin E. Furthermore, SIT induced local and systemic IL‐10‐producing Treg cells and regulatory NK cells. Conclusion: We established a SIT model on AD mice and showed that our model correlates well with previous reports about SIT‐treated patients. Also, we revealed NK cells as another possible resource of IL‐10 in SIT. Based on our results, we suggest our SIT model as a useful tool to investigate mechanism of action of SIT and to validate the efficacy of new SIT modalities for the treatment of AD.